Answer:
x = -2
Step-by-step explanation:
![f(x) =x^2 -2x\:\: and \:\: g(x) = 6x + 4\\(f+g)(x) = f(x) + g(x) \\(f+g)(x) = x^2 -2x+ 6x + 4\\(f+g)(x) = x^2+4x + 4\\(f+g)(x) = (x+2)^2\\ 0 = (x+2)^2...[\because (f+g)(x) =0]\\0 = x+2\\\therefore x = -2](https://tex.z-dn.net/?f=f%28x%29%20%3Dx%5E2%20-2x%5C%3A%5C%3A%20and%20%5C%3A%5C%3A%20g%28x%29%20%3D%206x%20%2B%204%5C%5C%28f%2Bg%29%28x%29%20%3D%20f%28x%29%20%2B%20g%28x%29%20%5C%5C%28f%2Bg%29%28x%29%20%3D%20x%5E2%20-2x%2B%206x%20%2B%204%5C%5C%28f%2Bg%29%28x%29%20%3D%20x%5E2%2B4x%20%2B%204%5C%5C%28f%2Bg%29%28x%29%20%3D%20%28x%2B2%29%5E2%5C%5C%200%20%3D%20%28x%2B2%29%5E2...%5B%5Cbecause%20%28f%2Bg%29%28x%29%20%3D0%5D%5C%5C0%20%3D%20x%2B2%5C%5C%5Ctherefore%20x%20%3D%20-2)
Here is a photo of how to solve it
Hi there! A = 78
A + 44 = B
We can plug in the values of A and B into the equation. We then get an equation with only one variable (x), which we can solve.
1x + 76 + 44 = - 6x + 134
Collect terms.
1x + 120 = - 6x + 134
Add 6x to both sides.
7x + 120 = 134
Subtract 120 from both sides
7x = 14
Divide both sides by 7
x = 14 / 7 = 2
A = 1x + 76
Now plug in the value of x we just found
A = 2 + 76 = 78